Fast Algorithms and Performance Bounds for Sum Rate Maximization in Wireless Networks - Chee Wei Tan; Mung Chiang; Srikant, R. (IEEE/ACM transactions on networking, 2013)
In this paper, we consider a wireless network where interference is treated as noise, and we study the nonconvex problem of sum rate maximization by power control. We focus on finding approximately optimal solutions that can be efficiently computed to this NP-hard problem by studying the solutions to two related problems, the sum rate maximization using a signal-to-interference-plus-noise ratio ( SINR ) approximation and the max-min weighted SINR optimization. We show that these two problems are intimately connected, can be solved efficiently by algorithms with fast convergence and minimal parameter configuration, and can yield high-quality approximately optimal solutions to sum rate maximization in the low interference regime. As an application of these results, we analyze the connection-level stability of cross-layer utility maximization in the wireless network, where users arrive and depart randomly and are subject to congestion control, and the queue service rates at all the links are determined by the sum rate maximization problem. In particular, we determine the stability region when all the links solve the max-min weighted SINR problem, using instantaneous queue sizes as weights.